Enhancing Financial Sector Surveillance in Low-Income Countries : Financial Deepening and Macro-Stability. (Policy Papers; Policy Paper, 2012)
This paper aims to widen the lens through which surveillance is conducted in LICs, to better account for the interplay between financial deepening and macro-financial stability as called for in the 2011 Triennial Surveillance Review. Reflecting the inherent risk-return tradeoffs associated with financial deepening, the paper seeks to shed light on the policy and institutional impediments in LICs that have a bearing on the effectiveness of macroeconomic policies, macro-financial stability, and growth. The paper focuses attention on the role of enabling policies in facilitating sustainable financial deepening. In framing the discussion, the paper draws on a range of conceptual and analytical tools, empirical analyses, and case studies.